Archaeology of the Digaru-Kolong River Valley with Special Emphasis on the Neolithic Period - Kumar, Jitendra (My University, 2023)
Northeast India has long been considered a significant region for archaeological research. The geographical setting, biodiversity, diverse ethnic culture, ancient settlement, and traces of migration play a crucial role in creating a dynamic landscape of Northeast India. Assam and Meghalaya are crucial regions for archaeological research in Northeast India. However, most of the research in the region has been limited to site-specific studies. The present study area of Digaru – Kolong river valley is located in the foothills of the Meghalaya plateau and is surrounded by several archaeologically potential regions, such as North Cachar Hills, Khasi, and Garo Hills. Sarutaru and Marakdola are the only reported and excavated sites in this region. The reports of accidental findings of artifacts are widespread throughout the region, which further indicates the potentiality in terms of archaeological research.
Sharma, Sukanya